Temporal variation and age influence activity budget more than sex and reproductive status in wild brown howler monkeys (Alouatta guariba clamitans) inhabiting a large, continuous forest - Mello, Isabella [UNESP]; Alvarenga de Oliveira, Claudio; Sobral, Gisela (Springer Nature, 2024)
Activity budget analyses are important for understanding how animals spend their time in daily activities like resting, foraging, moving and socializing. These behaviors are closely linked to energy management, so habitat quality and resource availability are known to influence the activity budgets of species. Therefore, many studies have examined the consequences of habitat loss and fragmentation on the energetic demands and activity budgets of species. However, we still have limited knowledge of how animals behave in large, continuous, and protected environments, as such habitats are currently rare. The present study analyzed how temporal variation, age, sex and reproductive status influenced the activity budget of wild red howler monkeys (Alouatta guariba clamitans), in one of the last Atlantic Forest remnants that remains large and protected. Between November 2017 and December 2018, we monitored two groups, G3 and G4, in Parque Estadual Carlos Botelho, São Paulo, Brazil. The groups were composed of one adult male, two adult females and their offspring and one (G3) or two (G4) subadult males, using scan sampling for behavioral for data collection every 20 min. The most common behavior was resting, followed by foraging, moving and social interactions, with inter-group differences. Temporal variation explained most of the fluctuations in the activity budget, so did age and sex, but to a lesser degree. The reproductive status of females did not alter their activity budget. These findings reveal that even neighboring groups display distinct and intricate relationships with their habitat. Future studies should be conducted in continuous forests to determine what is the expected range of variation in activity budget, particularly in those species considered as flexible and inhabiting endangered habitats, such as the Atlantic Forest.
Keywords: Behavior patterns; Energy budget; Neotropical primates; Platyrrhini